مابعد نوآبادیات کی جمالیات کی تشکیل میں فرانز فینن کا کردار (Al-Qamar, 2018)
Post Colonialism is a postmodern literary theory. Frantz fanon’s writings played an important role in the formation of the aesthetics of the theory of postcolonialism. In his writings, there is a detailed discussion of the strategy adopted to sustain the colonialism by colonizer. He also analyzed the settler’s indigenous relationship with colonies. He suggests an alternative path of resistance for Third World nations, the path, that will lead to true freedom. Franz Fanon has analyzed common narratives of colonizer which were being created to captivate them for longer time period. According to Fanon, violence is the defining characteristic of colonialism, which can be equally practiced by natives for liberation.
Keywords: Frantz Fanon; Postcolonial Aesthetics